Studi Literatur Penerapan Project-Based Learning (PjBL) pada Pembelajaran Kimia - Nabilah Mustika Putri; Lukman El Hakim; Rizhal Hendi Ristanto (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The relationship between constructivist theory and Project-Based Learning (PjBL) is very close, as both share many of the same fundamental principles. The aim of this study is to determine the effectiveness and impact of implementing Project-Based Learning (PjBL) in learning chemistry. The method used in this study is a Systematic Literature Review (SLR) with Google Scholar. The results of this study indicate that the implementation of Project-Based Learning (PjBL) in chemistry learning has a significant impact on improving students' understanding, as well as developing critical thinking and collaborative skills. Project-Based Learning (PjBL) places students at the center of the learning process, allowing them to connect theory with practice through relevant and challenging projects. PjBL also impacts positively on students' collaborative skills. It also enhances students' motivation and engagement in chemistry learning. Since PjBL is centered on projects that are relevant and meaningful to students, they are much more motivated to be actively involved in the learning process. In order to ensure that the implementation of Project-Based Learning (PjBL) in chemistry learning is more effective and relevant to the needs of today's learners, teachers may utilise technology platforms such as Zoom, Google Classroom, or other online learning applications to facilitate collaboration and interaction between learners by online.